2020
DOI: 10.1002/adfm.202007894
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐Femtojoule‐Energy‐Consumption Conformable Synaptic Transistors Based on Organic Single‐Crystalline Nanoribbons

Abstract: Inspired from powerful functionalities of human brain, artificial synapses are innovated continuously for the construction of brain‐like neuromorphic electronics. The quest to rival the ultralow energy consumption of biological synapses has become highly compelling, but remains extremely difficult due to the lack of appropriate materials and device construction. In this study, organic single‐crystalline nanoribbon active layer and elastic embedded photolithographic electrodes are first designed in synaptic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 57 publications
0
47
0
Order By: Relevance
“…Figure S6(b), Supporting Information illustrates the energy requirement of the MXFGT for the complete relearning process after different voltage erasing processes. The energy consumption of the synaptic device could be calculated through the equation below [12] :…”
Section: Resultsmentioning
confidence: 99%
“…Figure S6(b), Supporting Information illustrates the energy requirement of the MXFGT for the complete relearning process after different voltage erasing processes. The energy consumption of the synaptic device could be calculated through the equation below [12] :…”
Section: Resultsmentioning
confidence: 99%
“…Besides the various functions and high stability of our synaptic transistor, the energy consumption has also been considered, which is an important feature of artificial synapses. For short‐term plasticity, the energy consumption per spike in Figure 3a is about 4×10 −9 J calculated with the formula I peak × t d × V DS , [ 19,24,26 ] where I peak , t d , and V DS represent the peak value of the EPSC (≈102 nA), the duration time of the pulse (80 ms), and the source–drain voltage (0.5 V), respectively. However, a weaker V DS of 0.05 V and a narrow pulse duration time (0.8 ms) also can induce the response of the device with an EPSC of ≈22 nA, as shown in Figure S8a, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] reported a flexible electrochemical neuromorphic organic device on polyethylene terephthalate (PET) substrates which is made by commercially available plastic materials. It was found that most devices employs organic materials, [ 24–27 ] transferred 2D materials flake, [ 28–30 ] or amorphous oxide [ 23,31,32 ] as functional compounds based on flexible substrate (polymer, paper and silicon membrane). Poorly, researches on array‐level flexible neuromorphic system has not been reported, which is attributed to the reliability, scalability and stability issues of flexible synaptic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Some artificial synapses that are operated at comparable power requirements as biological synapses have been successfully designed as well. For instance, an organic synaptic transistor showed superior sensitivity and minimum energy consumption to external stimuli of, as little as, 10 mV [ 123 ] and 0.29 fJ, [ 124 ] respectively. In the future, organic synaptic devices with low energy consumption, multi‐function, high sensitivity, and high‐density integration will be one of promising unit in the artificial intelligent computer of similar to human brain.…”
Section: Discussionmentioning
confidence: 99%